Intestinal barrier dysfunction induced by ammonia exposure in pigs in vivo and in vitro: The protective role of L-selenomethionine - Xinxin Zhang; Anqi Wang; Ying Chen; Jun Bao; Houjuan Xing (Ecotoxicology and Environmental Safety, 2022)
Ammonia has been reported to have a variety of toxicity to aquatic animals, farm animals and humans. However, its potential toxicity on the intestines remains unknown. L-selenomethionine is one of the important organic selenium sources. However, the mitigating effect of L-selenomethionine on ammonia exposure toxicity is still lacking. Therefore, in this study, the mechanism of toxic action of ammonia on intestinal tract and the detoxification effect of L-selenomethionine were examined. We evaluated the intestinal toxicity of ammonia and the alleviating effect of L-selenomethionine in an in vivo model, and then verified it in vitro model by a variety of cutting-edge experimental techniques. Our results showed that ammonia exposure causes oxidative stress, necroptosis, Th1/Th2 imbalance and inflammation in the intestinal tissue and the intestinal cells, and L-selenomethionine had a significant mitigation effect on the changes of these indexes induced by ammonia. In conclusion, ammonia exposure caused oxidative stress and Th1/Th2 imbalance in the porcine small intestine and IPEC-J2 cells, and that excessive ROS accumulation-mediated necroptosis targeted inflammatory responses, resulting in the destruction of tight connections of intestinal cells, thereby causing intestinal barrier dysfunction. L-selenomethionine could effectively reduce the intestinal injury caused by ammonia exposure and antagonize the toxic effect of ammonia.